Exploration of the pattern, clinical presentation and outcome of children with renal diseases: A 14-year retrospective study at a teaching hospital in Ghana - George Nkrumah Osei; Emmanuel Worae; Betty Effie Adoko Ghartey; Perditer Okyere; Felix Abekah Botchway; Sampson K. Djonor; Richard K.D. Ephraim (PLoS ONE, 2025)
Introduction Paediatric nephropathy, a condition associated with significant morbidity and mortality, is increasing in developing countries. Data on children with renal diseases are insufficient in Ghana despite the risk it poses. This study assessed the pattern, spectrum, outcome, and predictors of dialysis and death among children with renal disease at Korle Bu Teaching Hospital (KBTH), Ghana. Materials and methods A cross-sectional retrospective review was conducted among children aged 0–17 years. Demographic characteristics, clinical and laboratory data, information on dialysis and treatment outcomes were obtained from their medical records and analyzed accordingly using STATA software version 15.1. Results A total of 332 children with renal diseases were seen (median age of 6 years), with 200(60.98%) being males. The most common renal diseases were nephrotic syndrome 141(42.47%) and acute kidney injury (AKI) 87(26.20%). Idiopathic (unknown) causes (82.98%) and intravascular hemolysis secondary to malaria (41.38%) were the major causes of nephrotic syndrome and acute kidney injury respectively. A death rate of 15.06% resulting mostly from AKI (6.33%) was observed whilst 7.83% underwent dialysis. Predictors of dialysis among those who had dialysis included being a female and having acute on chronic kidney disease whilst having high white blood cell count and acute on chronic kidney disease were significant predictors of death among children with renal diseases. Conclusion Paediatric renal diseases at KBTH were dominated by nephrotic syndrome and AKI. Timely treatment and prevention of common infectious agents and conditions causing intravascular hemolysis, which can contribute to paediatric renal diseases in Ghana, is needed to help reduce their progression to various forms of kidney disease.